RELEVANSI KONSEP PENDIDIKAN BERBASIS BUDAYA â€œSISTEM AMONGâ€ UNTUK PENGEMBANGAN MADRASAH IBTIDAIYAH - Sholeh, Ahmad (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
The concept of Among system is a education system that support values of humanities and democracy. It is still relevant to be implemented in Islamic education for future. The analyzing showed that the concept of Among system will bring a new paradigm in the learning process of Islamic education to make a revolution from traditional learning process.Â In the new paradigm, teacher is not only one source of science but also the student must have a critical thinking. So that, curriculum development of Islamic education will be centered in skill and transfer the values of religion.